Pullulan–Apple Fiber Biocomposite Films: Optical, Mechanical, Barrier, Antioxidant and Antibacterial Properties - Luís, Ângelo (2021)
More than 150 million tons of synthetic plastics are produced worldwide from petrochemical-based materials, many of these plastics being used to produce single-use consumer products like food packaging. The main goal of this work was to research the production and characterization of pullulan–apple fiber biocomposite films as a new food packaging material. The optical, mechanical, and barrier properties of the developed biocomposite films were evaluated. Furthermore, the antioxidant and antibacterial activities of the biocomposite films were additionally studied. The results show that the Tensile Index and Elastic Modulus of the pullulan–apple fiber films were significantly higher (p-value < 0.05) when compared to the pullulan films. Regarding the water vapor permeability, no significant differences (p-value < 0.05) were observed in water vapor transmission rate (WVTR) when the apple fiber was incorporated into the biocomposite films. A significant increase (p-value < 0.05) of water contact angle in both sides of the films was observed when the apple fiber was incorporated into pullulan, indicating an increase in the hydrophobicity of the developed biocomposite films. It is worth noting the hydrophobicity of the (rough) upper side of the pullulan–apple fiber films, which present a water contact angle of 109.75°. It was possible to verify the microbial growth inhibition around the pullulan–apple fiber films for all the tested bacteria.